Design and photovoltaic characterization of dialkylthio benzo[1, 2-b:4, 5-b′]dithiophene polymers with different accepting units. Issue 12 (26th February 2015) - Ge, Guidong; Gu, Jinan; Yu, Jiangsheng; Zhu, Enwei; Hai, Jiefeng; Bian, Linyi; Zhang, Fujun; Xu, Zhongsheng; Ma, Wanli; Tang, Weihua
Abstract : Three dialkylthio benzo[1, 2- b :4, 5- b ′]dithiophene polymers were developed with tuned bandgaps exhibiting a highest PCE value of 5.63% obtained for the polymer solar cells. Abstract : Three dialkylthio benzo[1, 2- b :4, 5- b ′]dithiophene (S-BDT) based polymers have been developed using different accepting units to tune their bandgaps. The polymer:PC71 BM solar cells achieved the highest power conversion efficiency (PCE) of 4.51% without any post-treatment (such as annealing and solvent additive) in conventional single-cell devices. Joint photophysical, electrical and computational studies on the polymer based solar cells revealed the considerable impact of molecular planarity on polymer design. The polymer:PC71 BM devices processed with 1, 8-diiodooctane for improving their morphology afforded an improved PCE value of 5.63%, with a V oc of 0.83, a J sc of 10.24 mA cm −2 and a FF of 66.3%.